2015
DOI: 10.1007/10_2015_307
|View full text |Cite
|
Sign up to set email alerts
|

Reactors for High Solid Loading Pretreatment of Lignocellulosic Biomass

Abstract: The review summarized the types, the geometry, and the design principle of pretreatment reactors at high solid loading of lignocellulose material. Among the reactors used, the explosion reactors and the helical stirring reactors are to be considered as the practical form for high solids loading pretreatment operation; the comminution reactors and the extruder reactors are difficult to be used as an independent unit, but possible to be used in the combined form with other types of reactors. The principles of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 79 publications
1
9
0
Order By: Relevance
“…This is in compliance with recent studies, e.g. Zhang et al [29,30] showing that solution containing up to 5 wt.% of glycerol had no negative effect on yeast fermentation. Insignificant glycerol concentrations were also noticed in current studies (< 1 g•dm -3 ) (data not shown), most probably as a by-product of ethanol fermentation by yeasts [31].…”
Section: Ethanol Production From Enriched In Cellulose Biomasssupporting
confidence: 93%
“…This is in compliance with recent studies, e.g. Zhang et al [29,30] showing that solution containing up to 5 wt.% of glycerol had no negative effect on yeast fermentation. Insignificant glycerol concentrations were also noticed in current studies (< 1 g•dm -3 ) (data not shown), most probably as a by-product of ethanol fermentation by yeasts [31].…”
Section: Ethanol Production From Enriched In Cellulose Biomasssupporting
confidence: 93%
“…However, the extent of process limitation is dependent on the various factors including the characteristics of biomass, the reactor configuration as well as operational conditions used. In this context, the evaluation of the different configurations of mechanically stirred reactors concomitant to the use of the fed-batch mode has been pointed out as an attractive strategy to overcome the rheological problems observed in SSF process at high biomass loadings [12,[33][34][35].…”
Section: Effect Of Solid Loading In Batch Ssfmentioning
confidence: 99%
“…The lower SL (10% SL) at 200C and 60 minutes gave higher glucose recovery. To overcome this, a specific reactor is needed [30].…”
Section: Solid Loading (Sl) Effectsmentioning
confidence: 99%